2017
DOI: 10.1097/pai.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Nestin as an Angiogenesis and Cancer Stem Cell Marker in Epithelial Ovarian Cancer: Immunohistochemical Study

Abstract: Ovarian cancer is the most fatal gynecologic malignancy and the existing second-line treatments have not been confirmed to be effective. Cancer stem cells research has a leading role to explore promising therapeutic applications. Nestin was postulated to reflect cancer stem cell properties in various tumors, correlating with poor prognosis. Furthermore, nestin is proposed as a reliable neovascularization marker. This study aimed to elucidate the status of nestin expression in various epithelial ovarian cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In the adult cardiovascular system, nestin is expressed in actively proliferating endothelial cells (EC), but is considered absent from mature vasculature 6 , 18 , 19 . Thus, it has been suggested as a potential therapeutic target for tumour-associated angiogenesis 18 , 20 23 and a prognostic marker 24 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In the adult cardiovascular system, nestin is expressed in actively proliferating endothelial cells (EC), but is considered absent from mature vasculature 6 , 18 , 19 . Thus, it has been suggested as a potential therapeutic target for tumour-associated angiogenesis 18 , 20 23 and a prognostic marker 24 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Expression of nestin in tumor cells was not associated with MVD-nestin (p > 0.05). In lesions with low expression pattern median values of nestin-positive MVD was slightly higher than in samples where staining reaction was moderate or high (22/HPF; range 13-37 vs. 19/HPF; range [12][13][14][15][16][17][18][19][20]. No significant correlation between MVD-CD34 and nestin-positive MVD (r = 0.14; p = 0.19) was found.…”
Section: Immunohistochemical Studiesmentioning
confidence: 74%
“…Nestin could serve not only as a reliable neovascularization marker but also may reflect cancer stem cell properties in different types of malignant masses, correlating with poor prognosis. Osman et al [20] found the expression of nestin in almost 50% of all epithelial ovarian cancers and this neurofilament protein was expressed more often (60%) in serous type of tumors. In our study nestin expression pattern in microvessels did not correlate with nestin expression in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between nestin expression in tumor tissue and the clinical course of the disease was reported for breast and ovarian cancers, as well as for gastrointestinal tumors, germ cell tumors, osteosarcomas and melanomas [10]. In some tumor types, increased nestin expression correlates with the tumor grade and indicates an immature and invasive phenotype of transformed cells [11,12]. Interestingly, the use of nestin as a predictive marker of a poor response to conventional therapy and to novel therapeutic agents was reported for multiple myeloma [13].…”
Section: Introductionmentioning
confidence: 95%
“…in tissue repair processes through proliferating vascular endothelial cells or in various malignant tumors. Previous studies showed that nestin could be another specific indicator of ovarian cancer aggressive and clinically advanced forms [11,12]. Correlation between nestin expression in tumor tissue and the clinical course of the disease was reported for breast and ovarian cancers, as well as for gastrointestinal tumors, germ cell tumors, osteosarcomas and melanomas [10].…”
Section: Introductionmentioning
confidence: 98%